(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Review of the book Corpo e(n)cena: ensaios urgentes, work organized by Jean Carlos Gonçalves, Sônia Machado de Azevedo and Renato Ferracini. This collection is part of the LiCorEs: Language, Body and Aesthetics Collection, featuring 8 essays and an afterword that focus, through multiple perspectives, on the urgencies and relationships of the body and scene in contemporary times.